Intracardiac Shunting and Stroke in Children: A Systematic Review - Dowling, Michael M. (J Child Neurol, 2011)
In adults, patent foramen ovale or other potential intracardiac shunts are established risk factors for stroke via paradoxical embolization. Stroke is less common in children and risk factors differ. The authors examined the literature on intracardiac shunting and stroke in children, identifying the methods employed, the prevalence of detectible intracardiac shunts, associated conditions, and treatments. PubMed searches with keywords related to intracardiac shunting and stroke in children identified articles of interest. Additional articles were identified via citations in these articles or in reviews. The authors found that studies of intracardiac shunting in children with stroke are limited. No controlled studies were identified. Detection methods vary and the prevalence of echocardiographically detectible intracardiac shunting appears lower than reported in adults and autopsy studies. Defining the role of intracardiac shunting in pediatric stroke will require controlled studies with unified detection methods in populations stratified by additional risk factors for paradoxical embolization. Optimal treatment is unclear.